Autophagy Is Involved in the Viability of Overexpressing Thioredoxin o1 Tobacco BY-2 Cells under Oxidative Conditions - Sabrina De Brasi-Velasco; Omar López-Vidal; María Carmen Martí; Ana Ortiz-Espín; Francisca Sevilla; Ana Jiménez (Antioxidants, 2021)
Autophagy is an essential process for the degradation of non-useful components, although the mechanism involved in its regulation is less known in plants than in animal systems. Redox regulation of autophagy components is emerging as a possible key mechanism with thioredoxins (TRXs) proposed as involved candidates. In this work, using overexpressing PsTRXo1 tobacco cells (OEX), which present higher viability than non-overexpressing cells after H2O2 treatment, we examine the functional interaction of autophagy and PsTRXo1 in a collaborative response. OEX cells present higher gene expression of the ATG (Autophagy related) marker ATG4 and higher protein content of ATG4, ATG8, and lipidated ATG8 as well as higher ATG4 activity than control cells, supporting the involvement of autophagy in their response to H2O2. In this oxidative situation, autophagy occurs in OEX cells as is evident from an accumulation of autolysosomes and ATG8 immunolocalization when the E-64d autophagy inhibitor is used. Interestingly, cell viability decreases in the presence of the inhibitor, pointing to autophagy as being involved in cell survival. The in vitro interaction of ATG4 and PsTRXo1 proteins is confirmed by dot-blot and co-immunoprecipitation assays as well as the redox regulation of ATG4 activity by PsTRXo1. These findings extend the role of TRXs in mediating the redox regulation of the autophagy process in plant cells.